Pertanggungjawaban Pidana Bagi Pelaku Prostitusi Online Berdasarkan Undang-Udang No. 11 Tahun 2008 - Wishnu Kurniawan; Lia Alistantia Wijaya (Journal of Judicial Review, 2016)
This thesis is motivated because prostitution online is very detrimental to the public and the perpetrators must be responsible to his actions. The ability of responsible associated with being a self-perpetrator. Their error element is an essential element that give a responsible for legal subjects.Issues that be discussed in this thesis is how the criminal responsibility for perpetrators of online prostitution in the perspective Undang-Undang No. 11 Tahun 2008 Tentang Informasi Dan Transaksi Elektronik and the one who should be responsible and charged according to the theory of criminal law sanctions against the crime of prostitution online.Author in this thesis use normative juridical research method so the research looked at the law as a doctrine or a set of normative rules (law in book). Author in this thesis get a data from the study library by reading, studying and citing legislation, books and literature relating to prostitution online.After the completion of the writing of this thesis, the authors came to the conclusion that criminal responsibility lies in the legal subject of each person and the real perpetrator who should be responsible and charged according to the theory of criminal law sanctions against online prostitution are a prostitute and their clients.